Insect meals in cat diets and their effects on digestibility, physiology, and gut microbiota - Lisenko, Karen Guttenkunst; Saad, Flavia Maria de Oliveira Borges; Oliveira, Maiara Rodrigues Duarte; da Silva, Thaiane Vieira; Dias, Daniel Souza; de Oliveira, Luiz Duarte; Júnior, Sudário Roberto Silva; Nascimento, Júlio Cézar dos Santos; Ribeiro, Apolônio Gomes; Zangeronimo, Márcio Gilberto; da Costa, Diego Vicente; Carvalho, Lucas Rannier Ribeiro Antonino; et al. (Frontiers in Veterinary Science, 2025)
Insects are a valuable source of nutrients, but little is known about their nutritional value for companion animals. In this study, we evaluated the inclusion of three insect meals in cat diets (Cinerea cockroach, CC; Madagascar cockroach, MC; and Superworm, SW) at two different levels (7.5 and 15%) on apparent digestibility coefficient (ADC), blood parameters, fecal pH, short-chain fatty acids (SCFA), branched-chain fatty acids (BCFA), phenol and indole production, and gut microbiota during six experimental periods of 15 days each. No differences were found for ADC, except for chitin in which MC registered the highest ADC. The fermentative product analysis showed that propionate displayed higher abundance in all insect treatments compared to the control group. Moreover, cats fed CC diet resulted in higher fecal butyrate while higher 4-methylphenol was registered in cats fed MC and SW diets. No significant differences were found for fecal pH and score, as well as no change in urea, creatinine, and blood count were registered. No differences were registered for total fecal SCFA, BCFA, phenol, and indole production compared to the control group or between insect meal fed groups. The fecal microbiota analyzed by gene 16S rRNA sequencing of cats did not register differences in alpha or beta diversity. In conclusion, dietary inclusion of insect meal up to 15% is a suitable alternative food for adult cats.